The Internalization of Local Wisdom Values of “Upacara Ngalungsur” as social studies learning resources - Sana; Widiyanti, Triani; Dianah, Lili (Institut Pendidikan Indonesia, 2022)
Local wisdom-based learning aims to instill knowledge and understanding of students as the younger generation so that they are able to contribute in maintaining and preserving the culture in the surrounding environment as a valuable national asset. Social studies learning can be used as the right means to internalize the values ​​of local wisdom that exist in the community. The purpose of this study is to shape the character of students through the values ​​of local wisdom in the ngalungsur heirloom ceremony that exists around the student's environment. The method used in this research is a qualitative approach. Data collection techniques used are through observation, interviews, and documentation. The results of this study are: 1). The tradition of Ngalungsur heirloom is a tradition that aims to maintain or care for heirlooms as a form of public respect for Sheikh Sunan Rohmat Suci who has spread Islam. In this tradition there are several implementation processions which include commemorating the birthday of the Prophet SAW, the Kubra pilgrimage, inheritance of inheritance, torch parade, heirloom lifting, rudat art performances, mass circumcision and finally heirloom washing. 2). The values ​​contained in the tradition of the ngalungsur heirloom ceremony are religious values, social values, and cultural values. 3). The internalization of local wisdom values ​​for the ngalungsur heirloom ceremony is by adjusting cultural values, religious values ​​and social values ​​with the basic competencies and materials contained in social studies textbooks. Therefore, the ngalungsur heirloom ceremony can be used as a source of social studies learning because it relates to the socio-cultural environment in the community contained in social studies learning.